2021
DOI: 10.1021/acsomega.1c01797
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the 3CL Protease and SARS-CoV-2 Replication by Dalcetrapib

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) 3CL protease is a promising target for inhibition of viral replication by interaction with a cysteine residue (Cys145) at its catalytic site. Dalcetrapib exerts its lipid-modulating effect by binding covalently to cysteine 13 of a cholesteryl ester transfer protein. Because 12 free cysteine residues are present in the 3CL protease, we investigated the potential of dalcetrapib to inhibit 3CL protease activity and SARS-CoV-2 replication. Molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In addition, Cys145 – His41 are the two catalytic dyad residues of 3CL pro to play an important role in the cleavage of SARS-CoV-2 polyproteins [ 58 ]. In addition, other research groups also reported the potential role of targeting Cys145 to design novel antivirals against 3CL pro [ 59 , 60 ]. Interestingly, we observed conserved binding site interactions ( Thr25, Met49, and Met165 ) in both these compounds during the 150 ns MD simulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cys145 – His41 are the two catalytic dyad residues of 3CL pro to play an important role in the cleavage of SARS-CoV-2 polyproteins [ 58 ]. In addition, other research groups also reported the potential role of targeting Cys145 to design novel antivirals against 3CL pro [ 59 , 60 ]. Interestingly, we observed conserved binding site interactions ( Thr25, Met49, and Met165 ) in both these compounds during the 150 ns MD simulation.…”
Section: Discussionmentioning
confidence: 99%
“…A control virus was passaged concomitantly in the absence of drug during all the selection procedure. At specified RDV concentrations, EC 50 values were determined by a plaque reduction assay ( 10 ), and the Nsp12 genotype was determined by PCR amplification followed by Sanger sequencing. In addition, complete sequences of viral genomes at selected passages were determined using a published SARS-CoV-2 protocol ( 11 ) and MinION flowcells on a GridION X5 sequencer (Oxford Nanopore Technologies).…”
Section: Textmentioning
confidence: 99%
“…In subsequent simulations, we observed that these hydrogen bonds were not stable and that CCG‐50014 instead formed new hydrogen bonds and stacking interactions with the residues H41, M49, E166, and Q189. While a limited work has gone into investigating covalent inhibitors that may form disulfide bonds with the catalytic cysteine residue, 64 other studies have focused on several potential covalent inhibitors 65 , 66 , 67 , 68 , 69 , 70 , 71 which may modify the catalytic cysteine residue of M Pro via a C‐S bond. The covalent inhibitors investigated in these studies formed interactions with the residues N142, G143, H164, E166, P168, and Q189, the residues that we also observed to interact with CCG‐50014 in our work.…”
Section: Resultsmentioning
confidence: 99%